DIET OF YOUNG PEOPLE WITH PREDIABETES - Тапешкина, Наталья Васильевна; Алексеева, Наталья Сергеевна; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2024)
The aim of the study – to evaluate the dietary pattern in young people with prediabetes. Material and methods. In 2022-2023, a randomized study was conducted 105 young people (aged 30-44 years) with prediabetes (58.1 % (n = 61) women, 41.9 % (n = 44) men). The control group included 70 healthy subjects (61.4 % (n = 43) women, 38.6 % (n = 27) men) aged 30-44 years, without prediabetes and components of metabolic syndrome, with normal body weight. The presence of bad habits, lifestyle features, motor activity and diet was assessed according to a specially developed questionnaire. Results. In young people with prediabetes, in comparison with the control group, disorders of clinical and metabolic status were established (abdominal obesity, insulin resistance, hyperlipidemia, hyperglycemia, systemic inflammation, arterial hypertension). The dietary intake of individuals with prediabetes was represented by carbohydrates with a high glycemic index or foods high in saturated fat (p < 0.01) and less protein (p = 0.008). At the same time, a general tendency towards a decrease in the consumption of fish and seafood, milk and fermented milk products, and dietary fiber was noted in the diet of young people. Conclusion. Early diagnosis and preventive measures based on lifestyle changes and dietary adjustments play an important role in managing early carbohydrate metabolism disorders and preventing both its progression and the development of type 2 diabetes and cardiovascular diseases.